ASSESSMENT OF HEAVY METAL CONCENTRATIONS AND PHYSICOCHEMICAL PARAMETERS IN SOILS OF SELECTED REFUSE DUMPSITES IN FIVE GEOGRAPHICAL ZONES OF LAFIA METROPOLIS, NIGERIA - Anzene, Solomon J.; Akpomie, Timothy M.; Aremu, Matthew Olaleke (FUDMA Journal of Sciences, 2024)
The disposal of solid wastes has become a very serious problem particularly in most Nigerian cities due to rapid population explosion and commercial activities. Lafia metropolis, the capital city of Nasarawa State, Nigeria is experiencing rapid urbanization as a result of population growth, and unplanned development accompanied by indiscriminate waste disposal. In this study, concentrations of heavy metals and physicochemical parameters from 20 soil samples each from selected refuse dumpsites in wet and dry seasons were determined using Atomic Absorption Spectrophotometer and Association of Official Analytical Chemists (AOAC) standard methods. The results showed that during the wet season the concentration of heavy metals; Hg (0.100 mg/kg – 0.367 mg/kg), Cr (0.117 mg/kg – 0.926 mg/kg), and Mn (0.480 mg/kg – 1.385 mg/kg) were above the maximum permissible limits (0.04 mg/kg), (0.2 mg/kg), (0.1 mg/kg) of World Health Organisation (WHO), and (0.0005 mg/kg for Hg) of National Environmental Standards Regulations Enforcement Agency (NESREA), while that of Pb, As, Fe, Zn, Cu and Ni were below the tolerable limits. In the dry season, the levels of concentrations of Hg (0.123 mg/kg - 0.345 mg/kg), Cr (0.067 mg/kg – 2.833 mg/kg), and Mn (0.702 mg/kg – 3.091 mg/kg) across the locations were also found to be above the tolerable limits. Except for nitrates in wet season (131.36 mg/L – 1,312.15 mg/L), phosphates (0.12 mg/L – 7.86 mg/L) and organic matter (2.19% w/w – 3.24 % w/w), dry season for nitrates (176.84 mg/L – 1,755.21 mg/L), phosphates (0.26 mg/L – 14.39 mg/L), organic matter...